Design, Synthesis, and In Vitro Antiplatelet Aggregation Activities of Ferulic Acid Derivatives - Peng-Xuan Zhang; Hang Lin; Cheng Qu; Yu-Ping Tang; Nian-Guang Li; Jun Kai; Guanxiong Shang; Baoquan Li; Li Zhang; Hui Yan; Pei Liu; Jin-Ao Duan (Journal of Chemistry)
In order to discover new compounds with antiplatelet aggregation activities, some ferulic acid (FA) derivatives were designed and synthesized. The in vitro antiplatelet aggregation activities of these compounds were assessed by turbidimetric test. The results showed that the target compound 7f had potent antiplatelet aggregation activity with its IC50 27.6 μmol/L, and 7f can be regarded as a novel potent antiplatelet aggregation candidate.